Comparison of the strength development of binary and ternary cements containing perlite powder - Sičáková Alena; Figmigová Erika; Špak Matej (Selected Scientific Papers: Journal of Civil Engineering, 2020)
Currently, the consumption of blended cements is increasing all over the world. This is due to environmental, technical and economic reasons. Among the additives mixed with ordinary Portland cement, ground granulated blast furnace slag and fly ash are of particular significance. However, some regions may lack standard additives, and vice versa, may be rich in natural pozzolans. This paper is focused on the perlite as a natural pozzolanic material which is locally available. This study presents the results of the application of perlite as a component of blended cements in different proportions, representing binary and ternary compositions, and compares it with standard additives (fly ash and ground granulated blast furnace slag). The time development of both compressive and flexural strength, including results of 2, 7, 28 and 90-day testing, is analyzed. Perlite binders show acceptable time development of strengths, which is comparable to conventional blended binders based on ground granulated blast furnace slag and fly ash and do not constitute a technological barrier. With a higher dose of perlite, the time increase in flexural strength is slower, but the rate of increase in compressive strength does not change substantially. Flexural strength of 4.1–6.2 MPa and compressive strength of 18.8–38.5 MPa are sufficient for a number of practical applications and are expected to meet the required limits. An improvement of strengths in the later period (90 days) was also confirmed.